Stock assessment of the demersal offshore fishery resources off the Karnataka coast - R.S., Biradar (Fishery Technology, 2021)
The total biomass of the demersal stocks in the depth range of 30-200m between 12Â°401 and 15Â°N latitudes in the Indian Exclusive Economic Zone is estimated to be a:round 1,23,000 metric tons (t). There is scope for doubling the present catch of about 40,000 t from demersal resources by extending exploitation to 50-200m depth zone. About 78% of this increase is expected to come from four species, namely, Nemipterus japonicus, Priacanthus macracanthus, Saurida tumbil and Arius spp.